Exploring the State of South African Schools Regarding the Right to Free Basic Education - (:unkn) unknown (My University, 2024)
During the apartheid regime in South Africa, many black and other coloured people were segregated both socially and educationally. After South Africa’s political independence in 1994, the constitution was amended where all people were allowed to enjoy every government benefit equally and this benefit includes the right to free basic education. As a form of a pseudo-retaliation, many people that live in the squatter camps seemingly believe that the government must make provision for free basic education to its people in which transportation, food, school uniforms, health care and other necessities must be provided as a part of the free basic education policy. Considering limited government resources, will it be possible to provide all South Africans and migrants that live in South free basic education? The purpose of the research is to revisit the interpretation of the constitutional policy on free basic education in South Africa. The researchers highlight the need for proper education on the meaning of the policy and its importance to the South African public. A quantitative research method was used to record responses from two public schools in Cosmo City. The research will contribute to a better perception about government and the use of its resources.
Keywords: African Research